Enlaços, conflitos e performances na Ilha Grande-RJ à luz da análise textual discursiva - Gomes, Giovanna Adriana Tavares (2025)
Located in Angra dos Reis-RJ, Ilha Grande is stage for several daily performances that constantly resignify its cultures and experiences, building a local identity under the influence of its communities, called “Terra” and New community in this research. Furthermore, not only is tourism on the island intrinsic to its daily life, it also settled there in the midst of production processes, transforming the territory that, for several other phases, housed a quarantine and penitentiary system that ended in 1994. In this sense, this work aims to understand the processes of changes in social relations, established analytically, through observations based on analytical categories of performances, conflicts of interest, and discourses of the communities (Terra and New community) regarding the resignification of social territories and cultural identities since the implosion of the prison in 1994 and the beginning of the practice of commercial tourism activity. To this end, Discursive Textual Analysis is used as a methodological support in order to understand the social phenomena established there. For this analysis, 4 (four) communities were chosen that have specific coexistence centers, interacting with the territory in light of its own developments. The phenomena are observed based on Victor Turner's Social Drama theories (1974), which encompasses crisis, expansion of the crisis, regeneration and, finally, rearrangement or split.